Biosynthesis of prodigiosin by white strains of Serratia marcescens isolated from patients. - Ding, M J (1983)
Serratia marcescens isolated from infected adults generally does not synthesize prodigiosin. Other investigators have reported that most clinical strains form a pigment if furnished with 4-methoxy-2,2'-bipyrrole-5-carboxyaldehyde (MBC), a precursor of prodigiosin. To determine whether the pigment was prodigiosin, we studied 65 white strains of S. marcescens isolated from patients. On the basis of response to MBC, we assigned the strains to one of three classes: class 1 (14 strains), strains remaining white; class 2 (48 strains), strains becoming gray or pink; and class 3 (3 strains), strains becoming blue. Ethanol extracts of bacteria of classes 2 and 3 did not behave like prodigiosin when acidified or alkalinized, and the pigment spectra were not similar to prodigiosin spectra. If strains of class 3 were furnished with MBC plus 2-methyl-3-amylpyrrole (MAP), the other immediate precursor of prodigiosin, the pigment synthesized was characteristic of prodigiosin. Strains of classes 1 and 2 responded identically to MBC plus MAP and MBC alone. Although the majority of S. marcescens white strains from patients formed pigments in the presence of MBC, the pigments were not prodigiosin. A few strains did synthesize prodigiosin, but only if furnished with both MBC and MAP.